Glucose variability and mode of anaesthesia in major noncardiac surgery (GlucoVITAL): study protocol for a randomised controlled trial - Henrike Janssen; Priyanthi Dias; Louise Hiller; Russell Hewson; Rupert M. Pearse; Nick S. Oliver; Shaman Jhanji; Gareth L. Ackland; Ashok Sundar; Islam Abousharkh; Priyanthi Dias; Jai Varale; et al. (BJA Open)
Background: Hyperglycaemia after noncardiac surgery occurs commonly and is associated with complications. The choice of maintenance anaesthesia may promote hyperglycaemia and increase glucose variability, both of which exacerbate inflammation and organ dysfunction. We hypothesise that total intravenous anaesthesia reduces glucose variability, particularly in individuals with insulin resistance or diabetes mellitus, and hence may reduce postoperative complications. Methods: This multicentre, randomised controlled parallel group trial will recruit 450 participants ≥50 yr undergoing elective noncardiac surgery. Participants will be randomly allocated in a 1:1 ratio (with minimisation) to receive either total intravenous anaesthesia or inhalation agents (typically sevoflurane) for maintenance of anaesthesia. The primary outcome is blood glucose, measured at prespecified timepoints (before, immediately after, and the morning after surgery). Continuous glucose monitoring (CGM; Dexcom G7) will commence at induction of anaesthesia for up to 10 days after surgery (or hospital discharge) to establish the reliability and accuracy of CGM compared with blood glucose measurements. Secondary outcomes include days alive and out of hospital within 30 days of surgery and postoperative complications (Clavien–Dindo grade ≥2). Absolute glucose and CGM-derived measures of glucose variability will be compared between participants who sustain, or remain free of, myocardial injury within 24 h of surgery, infectious complications within 30 days of surgery, and vasopressor use persisting >4 h after surgery. Conclusions: GlucoVITAL will establish whether the mode of anaesthesia may alter glucose control in susceptible individuals and also explore the role of glucose variability in organ injury after noncardiac surgery using CGM. Clinical trial registration: ISRCTN46862025.